Penggunaan Model Problem Based Learning Berbantuan Kuis Kahoot Untuk Meningkatkan Hasil Belajar Siswa Pada Matematika Materi Sudut Di Kelas V SD Inpres Nunbaun Delha - Siti Hajar Kartini; Wara Sabon Dominikus; Adam Bol Nifu Benu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The research entitled "Using Problem Based Learning Model Assisted by Kahoot Quiz to Improve Student Learning Outcomes in Mathematics on Angle Material in Class V SD Inpres Nunbaun Delha" is motivated by the low learning outcomes of class V A students in the 2025/2026 academic year, especially in mathematics. This study aims to improve student learning outcomes in mathematics on angle material in class V SD Inpres Nunbaun Delha by using the Problem Based Learning (PBL) model assisted by Kahoot quiz. The research approach used is Classroom Action Research (CAR). The subjects in this study were all 25 class V A students of SD Inpres Nunbaun Delha, consisting of 7 male students and 18 female students. The data collection techniques used were observation, tests, and documentation using observation sheets and test questions as research instruments. The data analysis technique used was quantitative data analysis by finding the average value and percentage of learning completion. The results of the study showed that in cycle I, the percentage of student learning completion was only 52%, but this increased significantly to 84% in cycle II. This demonstrates that the use of a problem-based learning model assisted by a Kahoot quiz is highly effective in improving student learning outcomes in Mathematics on angles in fifth-grade students at SD Inpres Nunbaun Delha.